The impact of K-lactobionate and Bacillus subtilis on soil water retention in sandy loam soils - Lincoln, Michael (Kansas State University, 2024)
Due to a combination of expanded agricultural production, global warming, and depleting water resources, semi-arid agricultural regions of the world have come under increased water stress. Such water stress results in less freshwater available for crop production and impacts the economic foundations of rural agricultural areas. One such area is the western part of Kansas. Western Kansas is an agriculturally dependent region that produces much of the nation’s crops. This area is located on top of the Ogallala aquifer, which is the water source for the large-scale irrigation farming that occurs in the area. However, due to its overuse, the aquifer has been in the process of depletion, with some areas reporting 100-foot drops in areas of pumpable water. This has spurred a need for water saving techniques. One such method is through improving soil water retention by adding amendments to the soil. Two amendments that show promise for retaining soil moisture and reducing water use requirements are Bacillus subtilis and K-lactobionate. B. subtilis is a Gram-positive bacteria that can wet soil through production of a biosurfactant molecules as secondary metabolites. K-lactobionate is a chemical compound produced from mixing lactobionic acid and KOH, and lactobionate derivatives are potentially available as a biproduct from the dairy industry. In this thesis, four studies were performed, with the goal of determining if K-lactobionate-B. subtilis amendments can be used to improve water penetration in soils, reduce runoff, and reduce water loss by increasing water retention during drought like conditions. First, water penetration and aggregation test of the two amendments in sandy loam soil was performed, which revealed that addition of a combination of K-lactobionate and B. subtilis reduced water penetration times to increase water infiltration into treated soils, and also caused the formation of large soil aggregates. B. subtilis and K-lactobionate was also studied as a means to reduce water evaporation in sandy loam soils through evaporation experiments. It was found that the addition of K-lactobionate with and without B. subtilis to the soil produced less evaporation and high water rention, while B. subtilis alone produced similar evaporation and water retention as unamended soil. Finally, an experiment testing the growth of B. subtilis when using K-lactobionate as a substrate showed that adding K-lactobionate could stabilize B. subtilis cells in otherwise nutrient-poor environments, suggesting that it could enhance the application of B. subtilis amendments while in soil or when added to irrigation water for distribution. Overall, the two paired amendments showed promise as a potential way to prevent water losses in cropland. Future studies in non-sterile environments more representative of cropland are needed as a next step to continue to evaluate the potential of these soil amendments.
Keywords: Soil water retention; Bacillus subtilis; K-lactobionate